The effect of resolution on viscous dissipation measured with 4D flow MRI in patients with Fontan circulation: Evaluation using computational fluid dynamics. Issue 12 (18th September 2015) - Cibis, Merih; Jarvis, Kelly; Markl, Michael; Rose, Michael; Rigsby, Cynthia; Barker, Alex J.; Wentzel, Jolanda J.
Abstract: Viscous dissipation inside Fontan circulation, a parameter associated with the exercise intolerance of Fontan patients, can be derived from computational fluid dynamics (CFD) or 4D flow MRI velocities. However, the impact of spatial resolution and measurement noise on the estimation of viscous dissipation is unclear. Our aim was to evaluate the influence of these parameters on viscous dissipation calculation. Six Fontan patients underwent whole heart 4D flow MRI. Subject-specific CFD simulations were performed. The CFD velocities were down-sampled to isotropic spatial resolutions of 0.5 mm, 1 mm, 2 mm and to MRI resolution. Viscous dissipation was compared between (1) high resolution CFD velocities, (2) CFD velocities down-sampled to MRI resolution, (3) down-sampled CFD velocities with MRI mimicked noise levels, and (4) in-vivo 4D flow MRI velocities. Relative viscous dissipation between subjects was also calculated. 4D flow MRI velocities (15.6±3.8 cm/s) were higher, although not significantly different than CFD velocities (13.8±4.7 cm/s, p =0.16), down-sampled CFD velocities (12.3±4.4 cm/s, p =0.06) and the down-sampled CFD velocities with noise (13.2±4.2 cm/s, p =0.06). CFD-based viscous dissipation (0.81±0.55 mW) was significantly higher than those based on down-sampled CFD (0.25±0.19 mW, p =0.03), down-sampled CFD with noise (0.49±0.26 mW, p =0.03) and 4D flow MRI (0.56±0.28 mW, p =0.06). Nevertheless, relative viscous dissipation between different subjects was maintained irrespective of resolution and noise, suggesting that comparison of viscous dissipation between patients is still possible.